Rationale and design of Healthy Kids Beyond the Bell: a 2x2 full factorial study evaluating the impact of summer and after-school programming on children’s body mass index and health behaviors - R. Glenn Weaver; Michael W. Beets; Elizabeth L. Adams; Andrew T. Kaczynski; Brian Chen; Bridget Armstrong; Sarah Burkart; Keagan Kiely; Aliye B. Cepni; James W. White; Olivia Finnegan; Meghan Savidge; et al. (Trials)
Abstract Background The Structured Days Hypothesis posits that structure protects children against obesogenic behaviors (e.g., physical inactivity, unhealthy dietary intake) and, ultimately, prevents the occurrence of excessive weight gain. The hours following school (i.e., 3–6 pm school days) and summer vacation are two “windows of vulnerability” when children may experience less structure. Programs that provide a healthy structured environment and may prevent BMI gain exist for both time periods (i.e., after-school programs and summer day camps). Unfortunately, these programs are cost prohibitive for children from low-income families to attend. This study will test the impact of providing vouchers to access existing, community-operated after-school and summer programs on BMI z-score, body composition, and obesogenic behaviors (i.e., physical activity, screen use, diet, and sleep) of children (5–12 years) from schools that primarily serve families with low income. Methods The study will employ a 2x2 factorial design. Participants (N = 480) attending 4 elementary schools in one school district will be randomly assigned to a no treatment control, after-school program voucher only, summer day camp voucher only, or after-school and summer day camp vouchers. Vouchers will cover the full cost of attending a pre-existing community-based after-school or summer camp program. The primary outcome (BMI z-score) will be measured at baseline (before end of school year, ~ May), 3-month follow-up (after summer, ~ August), and 12-month follow-up (end the following school year, ~ May). Secondary outcomes include body composition (i.e., whole-body fat mass, fat free mass, and percent body fat) and obesogenic behaviors (i.e., physical activity, sedentary time, sleep, screen-time, and diet). The study will also employ a rigorous process evaluation which will consider after-school and summer camp program attendance and content. Analyses will examine differences between the four groups in BMI z-score, body composition, and obesogenic behaviors. Incremental cost effectiveness ratios will determine the cost effectiveness of the intervention. Discussion The current study will provide critical information for researchers, practitioners, and policy makers seeking to combat the childhood obesity epidemic in children from families with low-income during the school year and summer. Trial registration NCT05880901 . Registered 27 May 2023.